The Essential Oil Constituents of the Fresh and Air-dried Phragmanthera incana (Schum.) Balle and Its Bioactivities - Odunayo Christy Atewolara-Odule; Olapeju O. Aiyelaagbe; Oseyemi O. Olubomehin; Sunday. O. Ajibade; Abdulrazaq O. Ogunmoye; Seide M. Akoro; Olaoluwa O. Olaoluwa (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Phragmanthera incana Schum (Loranthaceae), used in ethnomedicine as a worm expeller and for treating diseases such as cancer and inflammation, had its essential oil constituents characterized and assessed for certain pharmacological activities. Gas Chromatography-Mass Spectrometry was used to analyze the essential oils extracted from fresh and dried P. incana leaves, flowers, and stems via hydrodistillation. Standard bioassays were employed to determine the antibacterial activity, cytotoxicity, anthelmintic effects on Pheritima posthuma, and antioxidant activity of the essential oils. Thirty-six and forty-five essential oil constituents were detected in fresh and dried P. incana, respectively. The percentage constituent in fresh P. incana follows the trend; flower > stem > leaf, a trend of stem > leaf > flower was observed in dried P. incana. The major volatile oils constituents of leaf, stems and flowers were fluoranthene (37.30%), hentriacontane (76.11%), and 3-methyl phenol (24.20%) respectively. All essential oils showed cytotoxicity, with fresh leaf oil having the lowest LC50 of 0.49 µg/mL. The essential oils of air-dried and fresh stem antibacterial activities were 20 mm for Bacillus aureus and 16 mm for Klebsiella pneumoniae compared to 10 mm by Gentamycin for both organisms. Compared to Menbendazole (63.55±1.12 to 90.55±0.97) at 100 mg/mL, all essential oils caused considerable worm paralysis and death (12.58±2.62 to 24.19±7.84 min). They also demonstrated moderate antioxidant potency, ranging from 41.67 to 85.98%. The essential oil components and biological activities are described for the first time. Bioassays’ results and presence of hentriacontane, phytol, gamma-sitosterol, stigmasterol, and tocopherol in the oils, support its traditional applications as anti-cancer, anti-inflammatory, anti-oxidant, and anthelmintic.